The Behavior of Infill Walls in RC Frames Under Combined Bidirectional Loading. Issue 4 (18th May 2016) - Misir, Ibrahim Serkan; Ozcelik, Ozgur; Girgin, Sadik Can; Yucel, Umut
Abstract : Large-scale reinforced concrete frames with five different infill conditions, namely three single-leaf, two double-leaf walls with and without Z-ties, and a bare frame were tested. Under progressively increased in-plane actions, as the main aspect the behavior of walls under simultaneously acting monotonic out-of-plane loads was investigated. All infill walls have doubled the initial stiffness and energy absorption capacity of the frames, and the ultimate strength has increased about 50%. Z-ties have helped the double-leaf wall to maintain its integrity up to higher inter-story drift levels, and improve the out-of-plane stability of the wall.